Using folktales : - Taylor, Eric K. (Cambridge university press, 2000)
Using Folk Tales shows teachers how to take advantage of the unique literary characteristics of folk tales to facilitate language learning. It provides over forty ready-to-use activities and dozens of stories. Activities are suitable for all ages and range from beginning to advanced.